2007
DOI: 10.1111/j.1740-1461.2007.00090.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Accuracy of Jury Verdicts

Abstract: Average accuracy of jury verdicts for a set of cases can be studied empirically and systematically even when the correct verdict cannot be known. The key is to obtain a second rating of the verdict, for example, the judge's, as in the recent study of criminal cases in the United States by the National Center for State Courts (NCSC). That study, like the famous Kalven‐Zeisel study, showed only modest judge‐jury agreement. Simple estimates of jury accuracy can be developed from the judge‐jury agreement rate; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
3
29
0
Order By: Relevance
“…Partially consistent with the findings in Spencer (), the results of the study showed that juries appeared to be more accurate than judges when the true verdict (as inferred by statistical methods) was not guilty, as indicated by greater values of true p ̂ 00 B | U relative to true p ̂ 00 A | U for Models 1 and 2. In turn, judges appeared to be more accurate than juries when the true verdict was guilty, as judges showed perfect accuracy by convicting the defendants; the corresponding statistic, true p ̂ 11 A | U , was 1.000 for all models, while true p ̂ 11 B | U ranged from 0.880 to 0.973.…”
Section: Results Of Data Analysessupporting
confidence: 87%
See 2 more Smart Citations
“…Partially consistent with the findings in Spencer (), the results of the study showed that juries appeared to be more accurate than judges when the true verdict (as inferred by statistical methods) was not guilty, as indicated by greater values of true p ̂ 00 B | U relative to true p ̂ 00 A | U for Models 1 and 2. In turn, judges appeared to be more accurate than juries when the true verdict was guilty, as judges showed perfect accuracy by convicting the defendants; the corresponding statistic, true p ̂ 11 A | U , was 1.000 for all models, while true p ̂ 11 B | U ranged from 0.880 to 0.973.…”
Section: Results Of Data Analysessupporting
confidence: 87%
“…Interestingly, Type II error rates for judges ( true p ̂ 01 A | U ) were invariably 0.000 for both models. These results suggest that while judges were making highly accurate decisions when the true verdict was guilty, they were more likely than juries to commit Type I errors when evidentiary strength was considered along with the judges' and juries' verdicts in the model, which replicates the results in Spencer ().…”
Section: Results Of Data Analysessupporting
confidence: 79%
See 1 more Smart Citation
“…The central problem is that, in real judgements about allegations of CSA by legal fact fi nders, there is rarely any criterion that can be used to judge the accuracy of fact fi nders' judgements, other than the evidence that was already known to the fact fi nders at the time they made their judgements. There are a number of interesting studies that have used indirect methods to provide rough estimates of the accuracy of verdicts rendered by judges and juries (Arkes & Mellers, 2002;Spencer, 2007); these studies suggest that jury verdicts in criminal cases may be signifi cantly less accurate than is commonly believed. A study of nine real-world criminal CSA cases in Sweden suggests that legal fact fi nders' judgements about the validity of CSA allegations are biased and unreliable when they are made on the basis of psychosocial evidence (Lindblad & Lainpelto, 2008).…”
Section: Should Evidentiary Thresholds For Substantiation and Criminamentioning
confidence: 98%
“…In addition to their use in diagnosing disease, such models are used in the social sciences. See for example Gastwirth and Sinclair (1998), and Spencer (2007).…”
Section: Introductionmentioning
confidence: 99%